Hydrocephalus and Dandy- Walker Malformation: a review - Patricia Alessandra Dastoli Dastoli; Jardel Mendonça Nicácio; Marcos Devanir Silva da Costa; Italo Capraro Suriano; Marcia Cristina da Silva; Sergio Cavalheiro (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction: Dandy Walker malformation (DWM) is characterized by agenesis or hypoplasia of the cerebellar vermis, cystic dilatation of the fourth ventricle leading to an increase of the posterior fossa and superior dislocation of the lateral sinus, tentorium and torcula. Although it is the commonest posterior fossa malformation, its pathogenesis is still not fully understood, making the differential diagnosis with other posterior fossa malformations difficult and as a result the choice of therapeutic strategy. Material and methods: An extensive review of the literature relating to Dandy Walker malformation was performed. Historical, genetic, embryologic, epidemiologic, clinical and radiological presentation, treatment and prognosis were revised. Conclusion: The correct diagnosis of Dandy Walker malformation can be made through careful interpretation of magnetic resonance imaging (MRI) and cerebrospinal fluid (CSF) flow studies. The choice of hydrocephalus treatment depends on whether there is aqueduct stenosis. And, although ventriculoperitoneal (VP) shunts have been the treatment of choice for many years, neuroendoscopic techniques such as endoscopic thirdventriculostomy and stent placement are being frequently performed lately.